Pull Out Photo Box with AR Technology in Supporting Mathematics Literacy in Deaf Crew Members - Mualamah, Naila Nafisatun; Lestari, Feri Puji; Anggreini, Cahyani Ayu; Yasinta, Elsa; Widiyawati, Widiyawati; Ubaidah, Nila (Universitas Islam Sultan Agung, 2024)
Abstract. Every citizen has the same right to receive quality education, including children with special needs who are deaf. Lack of functioning of the sense of hearing causes children to be unable to imitate spoken words accurately and clearly, which results in ineffective communication. This research aims to develop a pull-out photo box with augmented reality technology as a visual medium to support mathematical literacy among deaf crew members. The research method used is Research and Development with a 3D development model. The data collection methods were observation, questionnaires, interviews, and test instruments. The instruments used include media expert and material expert instruments, teacher and student response instruments, and pretest and posttest questions. The data analysis used is a validity test, practicality test, effectiveness test (normality test, T-test (paired t-test), and N-Gain test). The research subjects comprised 7 grade VI students at the Anak Hebat Foundation Semarang. The research results show that using pull-out photo boxes effectively increases the mathematical literacy of deaf ABK students, with a significant difference in mathematical literacy abilities before and after using this media. Expert validation also shows that the learning media is very valid. This research also confirms that pull-out photo boxes are convenient, as analyzed by teacher and student responses.Keywords: pull-out photo box, mathematical literacy, and deaf